Fantastične pripovedi Astrid Lindgren - Petelinc, Saša (Revija za elementarno izobraževanje, 2009)
Astrid Lindgren's fantastic tales. The fantastic tale is the genre of youth literature that was separated from folk and fairy tales around 1930. Research done on this topic by literary analysts include Anne Krüger, Lucia Binder, Gote Klingberg and Helmut Müller. The theory of the fantastic tale is introduced in the books of Astrid Lindgren, who has been the subject of the first research done on this newly formed genre. The fantastic tales that are translated are: The Brothers Lionheart, Karlsson on the Roof, Pippi Longstocking and Ronja, the Robber's Daughter. The article also contains analyses of literary figures, comparisons and common characteristics that can be traced throughout all of Astrid Lindgren's youth literature.